Thalamocortical-auditory network alterations following cuprizone‐induced demyelination. Issue 1 (December 2016) - Ghaffarian, Nikoo; Mesgari, Masoud; Cerina, Manuela; Göbel, Kerstin; Budde, Thomas; Speckmann, Erwin-Josef; Meuth, Sven; Gorji, Ali
Abstract Background Demyelination and remyelination are common pathological processes in many neurological disorders, including multiple sclerosis (MS). Clinical evidence suggests extensive involvement of the thalamocortical (TC) system in patients suffering from MS. Methods Using murine brain slices of the primary auditory cortex, we investigated the functional consequences of cuprizone-induced de- and remyelination on neuronal activity and auditory TC synaptic transmission in vitro. Results Our results revealed an impact of myelin loss and restoration on intrinsic cellular firing patterns, synaptic transmission, and neuronal plasticity in layer 3 and 4 neurons of the auditory TC network. While there was a complex hyper- and depolarizing shift of the resting membrane potential, spontaneous and induced action potential firing was reduced during demyelination and early remyelination. In addition, excitatory postsynaptic potential amplitudes were decreased and induction of LTP was reduced during demyelination. Conclusions These data indicate that demyelination-induced impairment of neurons and network activity within the TC system may underlie clinical symptoms observed in demyelinating diseases, corroborating human findings that disease progression is significantly correlated with microstructural tissue damage of the TC system. Further investigation into focal inflammation-induced demyelination modelsex vivo and in vivo are needed to understand the functional implication of local and remote lesion formation on TC network activity in MS.